The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1590/s1516-89132013000500010
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of adhesion and aggregation abilities of four potential probiotic strains isolated from guppy (Poecilia reticulata)

Abstract: The aim of this work was to study the probiotic-related characteristics of four strains of bacteria isolated from the normal flora of the guppy, Poecilia reticulata. In vitro results showed that the strains, namely, MBTU_PB1, MBTU_PB2, MBTU_PB3 and MBTU_PB4 had higher adhesion abilities than the tested indicator strains. However, an association between the cell-surface hydrophobicity and the ability to adhere to the intestinal mucus was not observed for these strains. Further, the selected strains were strongl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
22
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 34 publications
(53 reference statements)
7
22
0
2
Order By: Relevance
“…The obtained results were in agreement with those reported by Blakrishma (36); as he showed that there is no correlation between these parameters. In another study, Lp9 isolate has surface hydrophobicity of 37-38%, suggesting its adhesiveness (37).…”
Section: Discussionsupporting
confidence: 92%
“…The obtained results were in agreement with those reported by Blakrishma (36); as he showed that there is no correlation between these parameters. In another study, Lp9 isolate has surface hydrophobicity of 37-38%, suggesting its adhesiveness (37).…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, the coaggregation and AAg were found to be directly related properties. The results are in agreement with earlier reports [6,36]. Nature of cell surface components of probiotics/pathogens may account for differences in coaggregation and AAg [1,2].…”
Section: Discussionsupporting
confidence: 93%
“…Coaggregation ability of probiotics with pathogens is considered as a desired property as it may play an important role in eliminating the pathogens from the GIT by preventing their attachment/lodging to the host tissue [35]. Varying level of coaggregation ability of the LAB isolates with different pathogens indicated that coaggregation potential is specific attribute that depends upon type of probiotic strain and the specific pathogens [36]. Furthermore, the coaggregation and AAg were found to be directly related properties.…”
Section: Discussionmentioning
confidence: 99%
“…The results revealed that aggregation, hydrophobicity and adhesion of LAB strains are strain‐specific and the correlations between autoaggregation and hydrophobicity, and autoaggregation and adhesion are positive among the nine L. lactis strains rather than the 18 strains belonging to different species tested. Therefore, bacterial aggregation and hydrophobicity can be used as a preliminary screening to assess their adhesion properties (Balakrishna ). In addition, porcine ileal epithelial cells were used in in vitro models to investigate aggregation and adhesiveness of Lactobacillus acidophilus M92 (Kos et al .…”
Section: In Vitro and Ex Vivo Studiesmentioning
confidence: 99%